Utilization of public health care facilities in Lucknow district - Shukla, Vinita; Agarwal, Monika; Idris, M. Z.; Ahmed, Naim; Gupta, Pratibha (International Journal Of Community Medicine And Public Health, 2018)
Background: Health has been declared a fundamental human right. Governments all over the world are striving to expand and improve their health care services. Though there is scarcity of health care resources in India, yet utilization of the Govt. Health care facilities reveal that their outreach was not only poor but even where they are within the reach of population they remained under utilization. In view of the facts stated above this study was planned to assess the extent of utilization of available health facility, the purpose of visit to health care facility and the reasons for non-utilization of public health care facility. Methods: Sample of 1024 was drawn from rural and urban population of Lucknow district. Cross sectional study was conducted in one-year period using the stratified multistage sampling. Data was analyzed using the stata software version -8 for windows. Results: Most of the respondents in rural (73.66%) and in urban (87.44%) visited the health facility for treatment of illnesses. Majority 55.28% in rural and 67.15% in urban area visited private health facility. The most common reason for non-utilization of public health facility in rural respondents (63.5%) was the long distance to health facility and for urban respondents it was long waiting time (56.46%). Conclusions: Most of the people prefer private health care facilities over public. The two most common reasons were long distance and long waiting time. These issues can be dealt by mobile clinics and strengthening the already existing health centres etc.